Effects of close reading academic texts on grade 11 students' reading comprehension and attitude toward reading - Sususco, Rachelle L. (College of Education, University of the Philippines Diliman, 2018)
The study examines how engaging students in the close reading comprehension and their performance in reading comprehension and their attitude towards reading. Two sections of grade 11 all female senior high school students taking up English for academic and professional purposes participated in this embedded study. As pre-test, a-pen-and-paper writing task was given to all students before the intervention to determine each students reading comprehension level. A pre-intervention was also conducted to determine students attitude towards reading. During the intervention, all participants were exposed to the same academic texts and were taught by the same teacher. Section A engaged in the close reading of academic texts only in the first four weeks of intervention. A pen-and-paper posttest and survey were given to all participants after the first four weeks of intervention and at the end of the intervention. The finding of the two posttest revealed that all the students could significantly improve their performance in reading comprehension, Most importantly, struggling readers showed remarkable improvements in reading comprehension. However, no significant change was observed in students attitude toward reading. The findings of this study confirmed two issues: first, the significant efficacy of integrating reading instruction for learners to better understand academic texts was verified at the end of the intervention. Second, teaching adolescents reading strategies could not automatically prompt a change in their attitude towards reading.